The Plastic People of the Universe - Chytilová, Jana (Czech Republic, 2002)
The film traces different stages in the history of the Czech rock band "The Plastic People of the Universe" and spans over more than 30 years of Czech history. Formed in 1968, following the Soviet invasion of Czechoslovakia, the band was inspired by American music banned by the Communist dictators including The Velvet Underground, Frank Zappa, Captain Beefheart and The Doors. The film tells their story via unique archival footage, photographs, performances, press coverage and interviews with the musicians and their friends, including Václav Havel and Lou Reed.
Donated by the Arts and Culture Program, CEU
Keywords: Documentary films